Compositional and functional gut microbiota alterations in mild cognitive impairment: links to Alzheimer’s disease pathology - Kang-Chen Fan; Chen-Ching Lin; Yen-Ling Chiu; Seong-Ho Koh; Yi-Chien Liu; Yi-Fang Chuang (Alzheimer’s Research & Therapy)
Abstract Background Emerging evidence highlights the bidirectional communication between the gut microbiota and the brain, suggesting a potential role for gut dysbiosis in Alzheimer’s disease (AD) pathology and cognitive decline. Existing literature on gut microbiota lacks species-level insights. This study investigates gut microbiota alterations in mild cognitive impairment (MCI), focusing on their association with comprehensive AD biomarkers, including amyloid burden, tau pathology, neurodegeneration, and cognitive performance. Methods We analyzed fecal samples from 119 individuals with MCI and 320 cognitively normal controls enrolled in the Taiwan Precision Medicine Initiative on Cognitive Impairment and Dementia cohort. Shotgun metagenomic sequencing was conducted with taxonomic profiling using MetaPhlAn4. Amyloid burden and plasma pTau181 were quantified via PET imaging and Simoa assays, respectively, while APOE genotyping was performed using TaqMan assays. Microbial diversity, differential abundance analysis, and correlation mapping with neuropsychological and neuroimaging measures were conducted to identify gut microbiota species signatures associated with MCI and AD biomarkers. Results We identified 59 key microbial species linked to MCI and AD biomarkers. Notably, species within the same genera, such as Bacteroides and Ruminococcus, showed opposing effects, while Akkermansia muciniphila correlated with reduced amyloid burden, suggesting a protective role. Functional profiling revealed microbial pathways contributing to energy metabolism and neuroinflammation, mediating the relationship between gut microbes and brain health. Co-occurrence network analyses demonstrated complex microbial interactions, indicating that the collective influence of gut microbiota on neurodegeneration. Conclusions Our findings challenge genus-level microbiome analyses, revealing species-specific modulators of AD pathology. This study highlights gut microbial activity as a potential therapeutic target to mitigate cognitive decline and neurodegeneration.